Teaching Factory Implementation Case Study in Beauty and Make up Competency - Rahmawati, Fitri; Fitrihana, Noor (Universitas Dharma Wacana, 2024)
The teaching factory is a production-based learning model designed to integrate educational environments with real-world industry practices. This model emphasizes collaboration between schools and industries to produce real products and services that are market-ready. By implementing this concept, students gain hands-on experience by directly practicing in laboratories or workshops. These sessions involve producing goods or services that are later sold to consumers, providing learners with practical exposure to the production and business process. The teaching factory concept bridges the gap between theoretical learning and industrial application. Students are not only taught academic content but are also equipped with essential skills for the workforce. This model ensures that they gain industry-relevant competencies, making them better prepared for future careers. Furthermore, it nurtures entrepreneurial skills by exposing students to real market dynamics and business challenges. This study focuses on exploring the implementation of the teaching factory model in SMK PGRI 1 Kudus. A qualitative research approach was employed, using a single case study method to deeply analyze the practice. Data collection techniques included a literature review, in-depth interviews, observations, and documentation. The researchers selected informants responsible for managing the teaching factory program at SMK PGRI 1 Kudus using purposive sampling. These informants provided key insights into the planning, execution, and challenges of the program. The findings of the study reveal that the effective implementation of a teaching factory program relies on three key pillars. First, real business operation is essential. This involves ensuring that the teaching factory simulates actual industry operations, enabling students to understand and engage with real-world production standards and market demands. For instance, products and services created in the teaching factory must meet the quality and pricing standards of the marketplace. This ensures that students grasp the importance of quality assurance and customer satisfaction. Second, a laboratory setting representation of related industries plays a critical role. The laboratory or workshop should closely replicate the conditions, equipment, and processes found in the industries students are being trained for. This alignment helps students familiarize themselves with the tools, technologies, and workflows they will encounter in professional settings. Moreover, such settings encourage a culture of innovation and problem-solving as students tackle tasks similar to those faced by professionals. Third, competence-based pedagogy forms the foundation of the teaching factory. This approach tailors the curriculum to industry standards, focusing on building specific competencies required in the workforce. Teachers act as facilitators, guiding students through experiential learning processes. The pedagogy emphasizes a balance between theory and practice, ensuring that students not only acquire knowledge but also develop the technical and soft skills needed for their chosen careers. In conclusion, the teaching factory model, as implemented in SMK PGRI 1 Kudus, demonstrates how education and industry collaboration can produce graduates who are both competent and competitive. By fostering real business operations, industry-representative settings, and competency-based learning, the program bridges the gap between education and employment, ultimately preparing students to thrive in the workforce.